2015
DOI: 10.1016/j.jclepro.2014.01.086
|View full text |Cite
|
Sign up to set email alerts
|

Improving the CO2 performance of cement, part III: the relevance of industrial symbiosis and how to measure its impact

Abstract: Improving the CO2 performance of cement, part III: The relevance of industrial symbiosis and how to measure its impact, 2015, Journal of Cleaner Production, (98) AbstractCement production contributes to extensive CO2 emissions. However, the climate impact can vary significantly between different production systems and different types of cement products. The market is dominated by ordinary Portland cement, which is based on primary raw materials and commonly associated with combustion of vast amounts of fossil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…In this article the term synergistic is used to describe this varying degree [cf. 29,30]. For example, the common centralized largescale production systems demanding huge amounts of feedstock from monoculture agricultural practices [31] cannot be seen as synergistic but rather linear.…”
Section: Resource Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In this article the term synergistic is used to describe this varying degree [cf. 29,30]. For example, the common centralized largescale production systems demanding huge amounts of feedstock from monoculture agricultural practices [31] cannot be seen as synergistic but rather linear.…”
Section: Resource Efficiencymentioning
confidence: 99%
“…Figure 2 illustrates schematically a linear (biofuel) production system and a more synergistic one. [29]). …”
Section: Resource Efficiencymentioning
confidence: 99%
“…The US Business Council for Sustainable Development has also worked with various states to create "By-product Synergy networks" that function in the same way [33]. Keeping with the themes of CO 2 and concrete, an analysis of the cement industry has shown that when cement producers are co-located with energy and steel industries, for example, there is enhanced potential for more sustainable practices such as including waste streams from the latter industries (such as fly ash) into blended cements as well as utilizing waste heat and/or using renewable energy [34].…”
Section: Industrial Symbiosismentioning
confidence: 99%
“…As a consequence, both the industry and academia are exploring strategies to minimise and/or capture CO 2 emissions and a wide portfolio of options appear feasible (Benhelal et al, 2013;Brunke and Blesl, 2014;Gao et al, 2014;Ishak and Hashim, 2014). One of the paths with great potential involves the use of alternative raw materials, preferably Cabearing so as to minimise the use of limestone, and the above may become more realistic and sustainable in an industrial symbiosis context (Ammenberg et al, 2014). Examples of industrial symbiosis already exist for decades, the use of ground granulated blast furnace slag and that of fly ash from coal-burning power plants, being two of the most well established.…”
Section: Introductionmentioning
confidence: 99%